Efficient spatial kelp biomass estimations using acoustic methods - Kartveit, Kyrre Heldal; Filbee-Dexter, Karen; Steen, Henning; Christensen, Lene; Norderhaug, Kjell Magnus (Frontiers in Marine Science, 2022)
Kelp forests are the largest vegetated marine ecosystem on earth, but vast areas of their distribution remain unmapped and unmonitored. Efficient and cost-effective methods for measuring the standing biomass of these ecosystems are urgently needed for coastal mapping, ocean accounting and sustainable management of wild harvest. Here we show how widely available acoustic equipment on vessels can be used to perform robust and large-scale (kilometer) quantifications of kelp biomass which can be used in assessments and monitoring programs. We demonstrate how to interpret echograms from acoustic systems into point estimates of standing biomass in order to create spatial maps of biomass distribution. We also explore what environmental conditions are suitable for acoustic measures. This has direct application for blue carbon accounting, coastal monitoring, management of wild seaweed harvest and the protection and conservation of marine habitats supporting high biodiversity.